Estudo do fosfogesso tratado termicamente e de suas misturas com solo tropical - Alves, Kárita Christina Soares Kanaiama (2015)
The phosphogypsum is a by-product of process for producing phosphoric acid in the phosphate fertilizers industries and its most common chemical composition is the same as gypsum (calcium sulphate dehydrate). Due to the large amounts produced daily studies are needed to enable its use. As research results, the phosphogypsum is already used in paving, as raw material blocks and boards, in cement industries, in sulphur recovery and sulphuric acid production, and is passed unprocessed to the agricultural sector. In this context, the main objective of this work was the study of phosphogypsum subjected to heat treated (TT) in mixtures with tropical soil in order to enable and expand its use in geotechnical works. To that end, it made the thermal treatment of phosphogypsum, which promotes its dehydration. For definition of mixtures were carried out Atterberg limits, compaction and expansion tests in samples containing soil, phosphogypsum TT and cement. The choice was made so that if using the highest percentage of phosphogypsum TT, since the samples having greater or equal to 7 plasticity index and expansion less than 0.5%. From this mixture, four mixtures were defined with tropical soil, phosphogypsum TT or dihydrate (DH), with or without cement. Miniature compaction tests were carried out with wet curing times of 5min, 25min and 2h so check their influence on compaction parameters of mixtures. In the analysis of hydromechanical behaviour, were carried out expansion testing, mini-CBR, expansability, simple compression test, slaking test and permeability test. To complement the analysis, scanning electron microscopy images were made, as also energy dispersive spectroscopy and testing of X-ray diffraction. For the reactions of phosphogypsum TT in the presence of water, the study of its rehydration was conducted and analysed the implications in its hydromechanical behavior. From the results it was observed that occurs the formation of hemihydrate and anhydrous gypsum by thermal treatment, and the formation of hemihydrate occurs from 110°C. The dry unit weight of mixtures with phosphogypsum TT decreases with increase of wet cure time, which is related to the growth of gypsum crystals during the rehydration process. The hydro-mechanical behavior of the mixtures containing phosphogypsum TT is better than those with DH phosphogypsum, and although rehydration occurs, the resistance of these mixtures are still higher than for mixtures containing phosphogypsum DH not subject to saturation. The mixture of soil and phosphogypsum TT showed high resistance, even after being subjected to saturation, which suggests that the cement used is unnecessary.